Parate Executie Polemic: The Nature of the Authority to Sell Creditors for Objects of Collateral Rights - Shohib, Muslim; Abid Zamzami (Jurnal Hukum dan Kenotariatan, 2023)
Execution of collateral objects is basically uncomplicated. The holder of the first Mortgage is also entitled to carry out direct execution of the object of the Mortgage that is used as collateral because in addition to the deed of Mortgage it also functions as proof of the existence of a Mortgage. Mortgage is a guarantee institution for land rights in the codification of national land law since the Mortgage Law was promulgated on April 9, 1996 , Mortgage rights function to provide protection for certain creditors and certain positions. where the deed is affixed with the irah-irah "For the sake of Justice Based on Belief in the One and Only God", which has executive powers which is the same as a court decision that has permanent legal force. Despite the fact that the auction procedure is likewise governed by a Minister of Finance Regulation, many lawsuits seeking the cancellation of auctions are nonetheless filed with the District Court on a regular basis. This research is included in the category of normative legal research, which analyzes laws and regulations in a comprehensive legal system. With regard to authority, in essence, an owner (eigenaar) has the power to control (beschikkingsbevoegdheid) and is authorized to act (handelingsbekwaanheid), but a person who is not an owner does not have power (beschikkingssonbevoegdheid) and may not act. Parate executie arrangements were prepared by legislators as a form of legal protection for the parties and are an excellent means of adjusting to legal requirements in the economic field.